2005
DOI: 10.1080/09546630500420183
|View full text |Cite
|
Sign up to set email alerts
|

Combination of oral terbinafine and topical ciclopirox compared to oral terbinafine for the treatment of onychomycosis

Abstract: Combination therapy of oral terbinafine and ciclopirox nail lacquer is a safe and more effective treatment for onychomycosis than terbinafine alone, especially in younger patients and in shorter-duration onychomycosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 12 publications
0
44
0
2
Order By: Relevance
“…While most onychomycosis studies focus on the great toenail, Shemer et al [25], found that there was a statistically significant difference in complete cure rates between the great toenail (23%), as compared to the second (65%), third (51%) and the fourth toenails (67%) [43]. This may be partially attributed to the fact that the hallux is more prone to external trauma [15,44,45] and thus more likely to be infected compared to healthy, non-deformed, toenails [46]. In addition, nail dystrophy may reduce penetration of the drug into its target.…”
Section: Nail Featuresmentioning
confidence: 94%
“…While most onychomycosis studies focus on the great toenail, Shemer et al [25], found that there was a statistically significant difference in complete cure rates between the great toenail (23%), as compared to the second (65%), third (51%) and the fourth toenails (67%) [43]. This may be partially attributed to the fact that the hallux is more prone to external trauma [15,44,45] and thus more likely to be infected compared to healthy, non-deformed, toenails [46]. In addition, nail dystrophy may reduce penetration of the drug into its target.…”
Section: Nail Featuresmentioning
confidence: 94%
“…118,119 Similarly, only limited increases in effi cacy are observed when daily oral therapy is combined with adjunctive therapy including once-weekly topical amorolfi ne or once-daily topical ciclopirox. [120][121][122][123] In each study topical therapy appeared to confer slight improvements in response; however, limited sample sizes restrict their signifi cance and superiority over terbinafi ne alone could not be determined.…”
Section: Onychomycosismentioning
confidence: 99%
“…Mycological cure rates for combination therapy were reported as 88%, 70%, and 70%, versus rates of 65%, 56%, and 82.6% for terbinafine monotherapy, respectively (42)(43)(44).…”
Section: Accepted Manuscriptmentioning
confidence: 99%